1999
DOI: 10.1126/science.283.5410.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Phosphate Crisis

Abstract: day be s u b m i i via e-mail (at scimce-let Paaasmg), fmc (202-789-4669)). or regular mail Science, 1200 New W krPnr% NW, W ion, DC 20905, USA). k t t e~~ are riot mutinely ~dolowledged. Full addresses, sigytuns, and laytime p h numbers should be included. ettm should be kief (300 wads or less) and n a y~~~f o r d a r l t y~w = ' l h e y m e y a p learinprkaandlorontheLntemctLetterwnt~areaotanrruttedkfacpuWcation rubrrriptienbr change of address, missing issues, new orlea and renewah and payment questiions. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
132
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(137 citation statements)
references
References 0 publications
1
132
0
4
Order By: Relevance
“…This is ecologically beneficial because P promotes eutrophication of fresh-water reserves (2) . The substrate, phytate, is present in all feedstuffs of plant origin predominantly as a Mg and K salt of phytic acid (myo-inositol hexaphosphate; IP 6 ), which may be represented as Mg 3 -K 6 -IP 6 ( 3) . Consequently, all practical pig and poultry diets contain variable concentrations of phytate, often in the order of 10 g/kg.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is ecologically beneficial because P promotes eutrophication of fresh-water reserves (2) . The substrate, phytate, is present in all feedstuffs of plant origin predominantly as a Mg and K salt of phytic acid (myo-inositol hexaphosphate; IP 6 ), which may be represented as Mg 3 -K 6 -IP 6 ( 3) . Consequently, all practical pig and poultry diets contain variable concentrations of phytate, often in the order of 10 g/kg.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the insolubility of mineral calcium phytate complexes at small-intestinal pH levels (4) in diets with conventional levels of Ca. Proximally, in the more acidic conditions of the stomach of pigs or the proventriculus and gizzard of poultry, phytate is relatively soluble and exogenous phytases have the capacity to hydrolyse IP 6 , at least partially at standard inclusion rates, thereby liberating inorganic P moieties. The enzymic degradation of phytate and the release of phytate-bound P, coupled with reductions in dietary P concentrations, combine to reduce P levels in excreta.…”
Section: Introductionmentioning
confidence: 99%
“…This situation has arisen because soybeans, grains and other plant seeds are used as the primary protein source in the animal feed . Approximately 80% of the organic phosphate in these seeds resides in InsP 6 , but the digestive lumen of these animals contains little or no phytase activity (Abelson, 1999;Mullaney et al, 2000). Thus, nutritional requirements necessitate that inorganic phosphate be added to the feed.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of data collected over 14 years revealed that the usage of global P fertilizer considerably increased at a rate of about 357,000 t/annum (i.e., an annual increase of 2.4%) [12,13]. Experts agree that the world is facing serious P crisis [14,15] and that the global P reserve is not distributed uniformly [5]. Taken together, these issues constitute compelling evidence justifying a direct link between Pi availability and the overwhelming world food security in coming few years.…”
Section: Introductionmentioning
confidence: 99%